2014
DOI: 10.1108/jeim-10-2012-0077
|View full text |Cite
|
Sign up to set email alerts
|

An integrated decision support system for ERP implementation in small and medium sized enterprises

Abstract: Purpose -Implementing ERP is a challenging task for small and medium sized enterprises (SMEs). This paper develops an integrated decision support system for ERP implementation (DSS_ERP) to facilitate resource allocations and risk analysis. Research limitations/implications -DSS_ERP proves to be beneficial to SMEs in identifying required resources and allocating resources, but could be further tested in case studies for its practical use and benefits.Practical implications -DSS_ERP serves as a useful tool for S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 34 publications
0
20
0
3
Order By: Relevance
“…Firm size is defined in a number of ways in the literature: by market capitalisation (de Villers et al, 2014;Brammar & Pavelin, 2008), number of employees (Tilley, 2000), and annual revenues (Gallo & Christensen, 2011 ) combined with number of employees (Coppa & Sriramesh, 2013;Perrini et al, 2007;Xie et al, 2014;Buonanno et al, 2005). In this study, the difference between small and large companies was indicated by annual revenue.…”
Section: Question 2: Investors Preference For the Quality Of Environmmentioning
confidence: 99%
“…Firm size is defined in a number of ways in the literature: by market capitalisation (de Villers et al, 2014;Brammar & Pavelin, 2008), number of employees (Tilley, 2000), and annual revenues (Gallo & Christensen, 2011 ) combined with number of employees (Coppa & Sriramesh, 2013;Perrini et al, 2007;Xie et al, 2014;Buonanno et al, 2005). In this study, the difference between small and large companies was indicated by annual revenue.…”
Section: Question 2: Investors Preference For the Quality Of Environmmentioning
confidence: 99%
“…In the academic literature, we have found frameworks that guide either some stages of EITA implantation or the entire process in the SME. We have classified the frameworks as follows: decision support [10], [11], preimplantation phase [12]- [15], selection [16], theoretical or conceptual frameworks [5], [17]- [22], cloud adoption [23], and holistic frameworks [24]- [27].…”
Section: Eita Implantation Modelsmentioning
confidence: 99%
“…Paper Jumlah Scheepers, 2016), (Maguire, Ab, & Maguire, 2010) Pengaruh stakeholder perspective pada penerapan (Saini et al, 2013), (Hogan, 2014), (Shaul & Tauber, 2012) (Finney, 2011), (Morris & Venkatesh, 2010), (Waiel AI-Rashid', 2012), (Maguire et al, 2010), (Shah, 2011), (Bintoro, 2015), (Ali & Miller, 2017), (Gallagher, Worrell, & Mason, 2012), (Boonstra & Boonstra, 2016), (Drummond & Araujo, 2016), (Matende & Ogao, 2013) 16 Studi Kasus (Saini et al, 2013), (Shaul & Tauber, 2012), (Finney, 2011), (Waiel AI-Rashid', 2012), (Maguire et al, 2010), (Shah, 2011), (Gallagher et al, 2012), (Boonstra & Boonstra, 2016), (Drummond & Araujo, 2016), (Xie, James Allen, & Ali, 2014) 10…”
Section: Kategorimentioning
confidence: 99%
“…Penerapan ERP pada UKM Pada sebuah penelitian (Xie et al, 2014) (Romero, Menon, Banker, & Anderson, 2010) Mahal dan memakan waktu yang lama dalam implementasi (Romero et al, 2010) Meningkatkan kepuasan karyawan melalui penghapusan redundansi dan kerepotan dari kegiatan sehari-hari. (Barker & Frolick, 2003) Perubahan budaya organisasi (penolakan pengguna).…”
Section: Estimasi Biaya Dan Durasi Waktuunclassified